Pengaruh Kinerja Keuangan, Kebijakan Dividen dan Umur Perusahaan Terhadap Nilai Perusahaan di Moderasi Ukuran Perusahaan - Muhammad Hamdani (Akuntansi & Ekonomika, 2020)
Study was conducted in the consumer goods industry sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2018. The aim is to determine the effect of financial performance, dividend policy, and age of the company on the value of the company which is moderated by the size of the company. The sample of 37 companies. The variables used are liquidity, capital structure, profitability, dividend policy, the age of the company to the value of the company with the size of the company as moderation. Results showed that there were influences on financial performance, dividend policy, company age, company size on firm value and company size able to moderate the influence of capital structure, profitability, dividend policy, company age on company value and company size unable to moderate the effect of liquidity on firm value.